INCREASE OF COMPETITIVENESS OF THE ENTERPRISE (EXAMPLE OF THE OIL PRODUCT MARKET) - Zh.Sh. Kydyrova,; К.B. Satymbekova,; G.E. Kerimbek,; G.Zh. Urazbayeva,; А.А. Shadieva, (Academic Journal of Physical and Chemical Sciences, 2019)
Today, the issue of competition is the main problem of a modern market economy. That is why there is a need for search and development of new methodological approaches in improving the competition mechanism of organizations involved in various areas of production activity, and processing enterprises in particular. In the current environment of business administration, it is necessary to develop new scientific approaches in identifying and substantiating indicators, strategies, analysis methods and evaluating the competitiveness of enterprises. During the period of development of the post-industrial economy there is a need in determining the formation of production potential and increase the competitiveness of the company, which shows the relevance of the studied problem. The aim of the study is to develop practical recommendations to improve the competitiveness of the company in the oil market.